Real Estate Market Price Prediction Model of Istanbul - Tekin Mert; Sari Irem Ucal (Real Estate Management and Valuation, 2022)
The Turkish Housing Market has experienced a steep increase in prices. Individual and corporate investors now possess tools to estimate the real estate evaluation while using smaller amounts of data with traditional techniques. Not having an analytical approach to evaluate the price of real estate could cause the investor to lose considerable amounts of money, especially in the case of individual investors. This study aims to determine how different machine learning algorithms with real market data can improve this process.